Chañaritos S-156: new chickpea cultivar (Cicer arietinum L.) - Biderbost, E. B. J.; Carreras, J. J. C. (Facultad de Ciencias Agropecuarias, 1991)
The wide genetic variability existing in populations of chickpea cv. Sauco was explored in order to obtain a cultivar with higher yield and better seed commercial quality. Three pure lines with improved quality were obtained: Chañaritos S-93, S-156 and S-159. Yield of these lines were compared in tests carried out for several years in various productive areas, and line S-156 was selected as the highest yielding one. The main characteristics of this new chickpea cultivar are the following: yield 1,800-1,900 kg/ha, mean seed size 0.49 g; seed shape lobulated, slightly furrowed; light yellow teguments, emergence-harvest interval 140-150 days; fair tolerance to Fusarium solani and F. oxysporum; resistance to low temperature (-5°C) especially during the vegetative period. This new cultivar is adapted to irrigated cultivation in soils with previous prolonged agricultural use.